Carrying Capacity Estimation of Herbicide-Treated and Untreated Palm Oil Plantation for Bali Cows - Eny Endrawati; Panjono Panjono; Bambang Suhartanto; Endang Baliarti (Buletin Peternakan, 2019)
This study aims to estimate the carrying capacity of oil palm plantations with the use of herbicides based on the forage availability for Bali cows. The research was performed in palm oil plantation owned by PTPN V Riau, from March 2016 until March 2017. The parameters observed were 1) Forage production that grows between palm trees at 6 weeks cutting age. The forage sample was taken from 5 point of 1x1m2, then subjected to proximate analysis. Data were analyzed with one-way random design, 2) Forage consumption; obtained by observation of 5 pregnant Bali cow and 7 non-pregnant for seven consecutive days 3). Estimated carrying capacity for Bali cows, obtained from the calculation of forage production (/ha/year) divided by forage consumption. The result of the research showed that 1). The production of dry matter (DM) forage in herbicide-treated areas was 689.55 kg/ha/year, not significantly different compared to untreated areas (622.33 kg/ha/year). Crude protein (CP) forage content of forage obtained from herbicide-treated area was significantly higher (p<0.05) than untreated area, whereas the total content of DM and total digestible nutrients (TDN) was not significantly different. DM consumption of pregnant Bali cow was on average 3.68±0.29 kg/head/day or 1,343.20±105.85 kg/head/year and non-pregnant 4.02±0.36 kg/head/day or 1,467.30±131.4 kg/head/year. The estimated carrying capacity on herbicide-treated (0.51 head of pregnant cow/ha), did not show any significant difference compared to untreated area (0.46 head/ha). For non-pregnant, the carrying capacity of herbicide-treated area (0.47 head/ha) was not different with non-treated area (0.42 head/ha). It was concluded that the use of herbicide on palm oil plantation had no effect on the carrying capacity of the Bali cow.